Shrink-Swell Soils of Palakkad District, Kerala: Their Characteristics and Classification - K.M. Nair, B.A. Dhanorkar, K.V. Niranjan, D.S. Mohekar and Arti Koyal, Jagdish Prasad1*, K.S. Anil Kumar (Journal of the Indian Society of Soil Science, 2021)
Representative pedons of Karuvapara series (P1) and Vannamada series (P2) from Palakkad district of Kerala were characterized and classified. The soils were very dark grayish brown to dark brown (P1) and very dark grayish brown to black (P2). The texture of the P1 varied from clay loam (Ap horizon) to clay and gravelly clay in sub-soils, while it was sandy clay (Ap horizon) to clay but sandy clay loam in last two horizons of P2. The pH of the soils in different horizon ranged from 7.1 to 8.2. Vannamada soils retained higher organic carbon (1.38% in Ap horizon) than Karuvapara soils. These soils had medium content of available N barring Ap horizon of P2 but high in available P (surface layer) and K. Available S, DTPA-Cu, DTPA-Fe, DTPA-Mn and hot water-soluble B in the soils were above the critical limit but DTPA-Zn was deficient except in Ap horizon of P2. These soils were classified as Typic Haplusterts (P1) and Vertic Epiaquepts (P2) at subgroup level.